Beyond counting cases: public health impacts of national Paediatric Surveillance Units. Issue 6 (11th December 2006) - Grenier, D; Elliott, E J; Zurynski, Y; Rodrigues Pereira, R; Preece, M; Lynn, R; von Kries, R; Zimmermann, H; Dickson, N P; Virella, D
Abstract : Paediatric Surveillance Units (PSUs) have been established in 14 countries and facilitate national, prospective, active surveillance for a range of conditions, with monthly reporting by child health specialists. The International Network of Paediatric Surveillance Units (INoPSU) was established in 1998 and facilitates international collaboration among member PSUs and allows for sharing of resources, simultaneous data collection and hence comparison of data from different geographical regions. The impact of data collected by PSUs, both individually and collectively as members of INoPSU, on public health outcomes, clinical care and research is described.